If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 = 1x + 4 Reorder the terms: -6 = 4 + 1x Solving -6 = 4 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -6 + -1x = 4 + 1x + -1x Combine like terms: 1x + -1x = 0 -6 + -1x = 4 + 0 -6 + -1x = 4 Add '6' to each side of the equation. -6 + 6 + -1x = 4 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = 4 + 6 -1x = 4 + 6 Combine like terms: 4 + 6 = 10 -1x = 10 Divide each side by '-1'. x = -10 Simplifying x = -10
| -8+8m+3=2m-22 | | x+1.2x=100 | | 2x+y=-44 | | 5(2x+4)=6(x-2) | | 99+4x=71 | | x^2+22x+40=(x+2)(x+20) | | (x+2)-6=188 | | Y=5t+4 | | 2p-2=9 | | P-2x/2=w | | 0.2x+0.7x=27 | | 6m+5=-(1-6m) | | x-6-2x=188 | | 4s+17=117 | | 5x+42=6x | | 2x-x=188 | | 6y-9=39 | | 6y-19=39 | | (6x^2y^4)(2xy)^3/12x^6y^8 | | X-0.32x=2.42 | | x+6+2x=188 | | (3x+1)(x-1)=15 | | 2x+5-x=-3x | | 1x-5y=4 | | 6+9=6-x | | 10(3x)-1=3-2y | | 2(3x+8)=2x-6 | | 6.25×12/5÷31.25×0.25 | | x+20=x-2+4x | | X^2-80x=0 | | 0.7(x+15)+0.4(x+25)=26 | | x+6-2x=188 |